2004
DOI: 10.5194/angeo-22-2515-2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolated electrostatic structures observed throughout the Cluster orbit: relationship to magnetic field strength

Abstract: Abstract. Isolated electrostatic structures are observed throughout much of the 4 R E by 19.6 R E Cluster orbit. These structures are observed in the Wideband plasma wave instrument's waveform data as bipolar pulses (one positive and one negative peak in the electric field amplitude) and tripolar pulses (two positive and one negative peak, or vice versa). These structures are observed at all of the boundary layers, in the solar wind and magnetosheath, and along auroral field lines at 4.5-6.5 R E . Using the Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 25 publications
14
128
0
Order By: Relevance
“…This is consistent with observvation of these solitons in magnetospheric plasmas [10][11][12][13] . Use the right hand side axis for the case when κ ∼ 3/2, which is very large compared to others.…”
Section: B Arbitrary κ -Numerical Solutionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with observvation of these solitons in magnetospheric plasmas [10][11][12][13] . Use the right hand side axis for the case when κ ∼ 3/2, which is very large compared to others.…”
Section: B Arbitrary κ -Numerical Solutionsupporting
confidence: 90%
“…In this section, we consider the physical scenario with two-temperature electrons, which is motivated by the experimental observations such as those by the Cluster spacecrafts 10 . We consider two species of electrons -hot and cold one.…”
Section: Two-temperature Electrons : Small Amplitude Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, they are commonly observed in auroral regions (Ergun et al, 1998; 2001; Pickett et al, 2004) but also in several Earth magnetic environments (Matsumoto et al, 1994;Franz et al, 1998;Cattell et al, 2003;Pickett et al, 2003) and in the Earth bow shock (Bale et al, 1998;Behlke et al, 2004). Evidence for the presence of isolated bipolar electrostatic structures in the solar wind is more recent: Mangeney et al (1999) first reported the observation of such structures in the free solar wind and Williams et al (2006) showed some examples associated to an interplanetary shock.…”
Section: Multipolar Electrostatic Structuresmentioning
confidence: 99%
“…The Cluster satellites have observed Electric Field Solitary (EFS) waves, moving parallel to the magnetic field direction, in many space plasma regions, such as the solar wind, magnetosheath, magnetotail, and in the auroral zone (Pickett et al, 2004;Marklund et al, 2004). Indeed, the EFS waves were first observed in the auroral zone by the S3-3 (Temerin et al, 1982) and Viking satellites (Boström et al, 1988).…”
Section: Introductionmentioning
confidence: 99%